A comparative investigation of seed storage protein fractions: The synergistic impact of molecular properties and composition on anisotropic structuring. (April 2023) - Nasrollahzadeh, Farzaneh; Roman, Laura; Skov, Kasper; Jakobsen, Louise M.A.; Trinh, Binh Minh; Tsochatzis, Emmanouil D.; Mekonnen, Tizazu; Corredig, Milena; Dutcher, John R.; Martinez, Mario M.
Abstract: Plant protein fractions are complex systems that could represent a versatile platform of building blocks for novel foods. The objective of this work was to evaluate potential common principles leading to anisotropy formation during wet extrusion by comparing different protein concentrates/isolates. Commercially available protein fractions (>63% protein) from different sources, namely pulses (pea, chickpea, fava bean and mung bean), cereals (gluten and rice), and oilseeds (soy and pumpkin), were individually extruded into a thermoplastic mass and comparatively investigated for composition, protein molecular properties, supramolecular interactions, visual anisotropy, rheology, and water mobility. This work shows that the structuring potential of plant protein fractions during thermomechanical processing should be explained by both molecular and colloidal mechanisms acting in concert and involving proteins, polysaccharides, and polyvalent ions. Wet extrusion resulted in the formation of new β -sheet structures in oilseed and cereal proteins through a higher extent of hydrogen bonds (extended β -sheets) and electrostatic interactions, as noted by X-ray photoelectron spectroscopy (XPS). Furthermore, disulfide bonds played a major role in protein-protein interactions. The presence of minerals facilitated the formation of complex coacervates, amenable to elongation during extrusion, enhancing anisotropy. Thus, pumpkin and mung bean extrudates, followed by soy, displayed the highest level of anisotropy, Warner-Bratzler tenderness and storage modulus ( E ′). These parameters were positively correlated (r > 0.8) with the proportion of newly formed ordered secondary structures ( β -sheets and α -helices). Graphical abstract: Image 1 Highlights: Extrusion-based structuring was explained by both molecular and colloidal mechanisms. Wet extrusion formed new β- sheet structures in oilseed and cereal proteins. Endogenous non-starch polysaccharides and minerals played a major structuring role. Mechanical properties were correlated (r > 0.8) with β -sheet and α -helix structures. Extrusion did not affect the content of free amino acids in any of the studied samples.